2019
DOI: 10.1101/19000497
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Proximal and distal factors predicting timely initiation of breast feeding in Ethiopia: a systematic review and meta-analysis

Abstract: Background: In Ethiopia, the current coverage of timely initiation of breast feeding (TIBF) has fallen short of the National Health Sector Transformation Plan 2016–2020, National Nutrition Program 2016-2020 and WHO global target. This calls for the need to assess relevant proximal and distal factors that affect the rate of TIBF in Ethiopia. Objective: The aim of this meta-analysis was to investigate the association between TIBF and educational status, household income, marital status, media exposure, and parit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…Additionally, one article was found by hand searching of the reference lists of the included studies. Thus, a total of 9 studies [4,[22][23][24][25][26][27][28][29] were included in the current umbrella review. The study selection and screening process is shown in Fig.…”
Section: Literature Search Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, one article was found by hand searching of the reference lists of the included studies. Thus, a total of 9 studies [4,[22][23][24][25][26][27][28][29] were included in the current umbrella review. The study selection and screening process is shown in Fig.…”
Section: Literature Search Findingsmentioning
confidence: 99%
“…Health [22][23][24][26][27][28][29] Lack of antenatal care Lack of postnatal care Place of delivery Sociodemographic [22][23][24][26][27][28][29] [26][27][28][29] Place of residence IYCF, Infant and young child feeding.…”
Section: Risk Factors Malnutritionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, one article was found by hand searching of the reference lists of the included studies. Thus, a total of 9 studies [4,[16][17][18][19][20][21][22][23] were included in the current umbrella review. The study selection and screening process is shown in Fig.…”
Section: Literature Search Ndingsmentioning
confidence: 99%
“…The speci c IYCF practice indicators assessed were exclusive breastfeeding, early initiation of breastfeeding, timely initiation of complementary feeding, dietary diversity, meal frequency, and minimum acceptable diet. Seven studies were done on both the magnitude and the determinants of IYCF practices [17][18][19][20][21][22][23]. The overall characteristics of the included studies, including the topic they addressed, is shown in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%